2020
DOI: 10.1111/psyg.12560
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality features and their association with mood symptoms and cognitive factors in a non‐clinical sample of older Brazilian adults

Abstract: Aim: There is strong interest in sleep disorders in the elderly, but there are gaps in identifying how multiple factors affect sleep quality in this population. We aimed to assess sleep quality and its relationship to mood, general cognition, and sociodemographic factors in a sample of cognitively active older adults. Methods: We assessed 105 non-clinical older adults (mean age AE SD: 69.64 AE 0.66 years) based on a sociodemographic profile questionnaire, the Beck Anxiety Inventory, the Beck Depression Invento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
(60 reference statements)
0
9
0
Order By: Relevance
“…Nonetheless, the results in this study must be carefully analyzed because its limitations prevent extrapolating its findings to other older people groups. The limitations identified in the present research include the sample size and characteristics, memory bias (as the instrument that assessed sleep quality was based on self-reported questions), ( 23 ) and factors such as stress, mood, fatigue, and level of physical activity (which may influence the HRV but were not assessed in this study). ( 28 )…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the results in this study must be carefully analyzed because its limitations prevent extrapolating its findings to other older people groups. The limitations identified in the present research include the sample size and characteristics, memory bias (as the instrument that assessed sleep quality was based on self-reported questions), ( 23 ) and factors such as stress, mood, fatigue, and level of physical activity (which may influence the HRV but were not assessed in this study). ( 28 )…”
Section: Discussionmentioning
confidence: 99%
“…( 7 , 22 ) The results of this study are similar to those observed in other pieces of research. In the study by da Silva et al ., ( 23 ) which also used the PSQI to assess sleep quality in older people, approximately 46.7% of them had poor sleep quality. In a multicentric study with older people, 68.5% of the subjects had a sleep disorder.…”
Section: Discussionmentioning
confidence: 99%
“…I-QOL was developed by Wagner et al in 1996 to determine the quality of life of patients with urinary incontinence. 24 The scale was revised by Patrick et al in 1999, and the number of items was reduced to 22 by removing six items by evaluating psychometric measurements during the creation of European versions. 25 In the study of Patrick et al, the Cronbach's alpha coefficient of I-QOL was found to be 0.95.…”
Section: Incontinence Quality Of Life (I-qol)mentioning
confidence: 99%
“…Previous studies on the Iranian elderly have similarly reported a high rate of poor sleep quality (75%) 36 . However, studies in other parts of the world have reported various rates, ranging from 25% in the USA 37 to approximately 45% in China 38 , 39 and Brazil 40 to 76% in community-dwelling older adults in Slovenia 41 , but the rates may be higher in nursing home residents (~ 95%) 41 , 42 . The difference in the sleep quality between countries may be due to differences in the economic status of the nations 43 .…”
Section: Discussionmentioning
confidence: 99%